Structural controls on the location and distribution of CO2 emission at a natural CO2 spring in Daylesford, Australia. (May 2019) - Roberts, Jennifer J; Leplastrier, Aero; Feitz, Andrew J; Shipton, Zoe K; Bell, Andrew F; Karolytė, Rūta
Highlights: Studies at natural CO2 seeps can inform effective monitoring design at CO2 stores. We examine the detailed characteristics of natural CO2 emission in a creek bed. CO2 preferentially emerges from foliated shales rather than fractured sandstone. Degassing locations are highly localized and determined by geological features. Gas bubbling into water is intermittent posing challenges to emission quantitation. Abstract: Secure storage of CO2 is imperative for carbon capture and storage technology, and relies on a thorough understanding of the mechanisms of CO2 retention and leakage. Observations at CO2 seeps around the world find that geological structures at a local and regional scale control the location, distribution and style of CO2 emission. Bedrock-hosted natural CO2 seepage is found in the Daylesford region in Victoria, Australia, where many natural springs contain high concentrations of dissolved CO2 . Within a few meters of the natural Tipperary Mineral Spring, small CO2 bubble streams are emitted from bedrock into an ephemeral creek. We examine the relationship between structures in the exposed adjacent outcropping rocks and characteristics of CO2 gas leakage in the stream, including CO2 flux and the distribution of gas emissions. We find that degassing is clustered within ˜1 m of a shale-sandstone geological contact. CO2 emission points are localised along bedding and fracture planes, and concentrated where these features intersect. The bubble streams were intermittent, which posed difficulties in quantifying total emitted CO2 . Counterintuitively, the number of bubble streams and CO2 flux was greatest from shale dominated rather than the sandstone dominated features, which forms the regional aquifer. Shallow processes must be increasing the shale permeability, thus influencing the CO2 flow pathway and emission locations. CO2 seepage is not limited to the pool; leakage was detected in subaerial rock exposures, at the intersection of bedding and orthogonal fractures. These insights show the range of spatial scales of the geological features that control CO2 flow. Microscale features and near surface processes can have significant effect on the style and location and rates of CO2 leakage. The intermittency of the bubble streams highlights challenges around characterising and monitoring CO2 stores where seepage is spatially and temporally variable. CCS monitoring programmes must therefore be informed by understanding of shallow crustal processes and not simply the processes and pathways governing CO2 fluid flow at depth. Understanding how the CO2 fluids leaked by deep pathways might be affected by shallow processes will inform the design of appropriate monitoring tools and monitoring locations.